Member - Gadanakis, Yiorgos (My University, 2026)
ICA-Edu SIG Entrepreneurship Education Workshop - Webinar: AI and entrepreneurship education, with a focus on social entrepreneurship held online on 9 Sept 2024 ICA SIG Educator Workshop: Implemneting challnge-based learning in sustainable eduaction allowing for the dvelopment of (sustainable) entrepreneurial competnecesImplemneting challnge-based learning in sustainable eduaction allowing for the dvelopment of (sustainable) entrepreneurial competneces held online on 26 April 2023 1st ICA-Edu SIG Colloquiun Putting Assessment of Sustainable Entrepreneurship Education in the Spotlight was held on 19 May 2022 5th ICA-Edu Colloquium Action to keep the entrepreneurial genie out of the bottle! Engaging students with sustainable entrepreneurial education in your curriculum was held online because of Covid-19 virus during the mornings of 26 to 28 May 2021. See the programme and presentations. See the Summary 4th ICA-Edu Colloquium: Let the entrepreneurial genie out of the bottle! how will we stimulate the nascent entrepreneurial skills of our students? was held on 15 and 16 May 2019 in Leuven, Belgium. See the Programme and Presentations. See the summary